Study on Fracturing and Diffusion Mechanism of Nonslab Fracturing Grouting - Hua Cheng; Xiangyang Liu; Jian Lin; Liangliang Zhang; Mingjing Li; Chuanxin Rong (Geofluids)
The coupling effect of a slurry and the fractured rock layer controls a spatial attenuation of the fracture channel width and grouting pressure from a grouting hole to the slurry top of fracture diffusion. This paper comprehensively considers the influencing factors such as the mechanical properties of the injected rock mass and the time-varying characteristics of the serous viscosity and introduces the control equation of the fracture channel width to establish a single-fracture nonslab fracturing grouting model. Combining the motion law of the slurry with the extension form of fracture, the equation of slurry diffusion motion, considering the fracture geometry and the time-varying characteristics of the serous viscosity, is derived. Comparing this equation with the existing theories and experiments, the validity and reliability of the theory are verified. In this paper, the effects of rock elastic modulus, slurry viscosity, and grouting rate on the fracturing grouting diffusion law of rock mass are analyzed. It is pointed out that when fracturing grouting in deep rock layers, a larger initial grouting rate and grouting pressure should be selected in the early stages of grouting to generate or penetrate fractures in the rock layer. Also, when the grouting pressure is stable, it is appropriate to increase the viscosity so that the slurry can quickly gel in the fractures thus sealing the fractures.